The opposition «my own/somebody else’s» in the short story by Lada Luzina «The Shadow of Demon» - Чёрный, Игорь Витальевич (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article is devoted to the activity of modern Ukrainian author Lada Luzina who writes her works in Russian. Her short story «The Shadow of Demon» which is a part of the cycle «Kiev witches» is examined. In particular, the reflection in the text the opposition «my own/somebody else’s» as one of the counterparts of the story’s main conflict has been analyzed. The binary oppositions such as West/East, Halloween/Old men, hell/abyss, paradise/Iriy, mask/face, carnival/funeral repast and others have been examined. The analysis of the main dichotomies in the short story by Lada Luzina «The Shadow of Demon» which are connected with the opposition «my own/somebody else’s» helps to understand and interpret the author’s intention.